Improvement of Performance Lemon Farmer Group in Marga Dajan Puri Village Marga District Tabanan Regency - MANUABA, I. B. Made Putra; SANJAYA, I Ketut Puja Wirya; GANAWATI, Nengah (PT Batara Swastika Harati, 2024)
Marga Dajan Puri Village is located in the Marga District of Tabanan Regency. The livelihoods of the village residents are quite diverse, with the majority engaged in agriculture and plantations. Based on the initiative of several villagers, they formed a group to cultivate Organic Seedless Israeli Lemon, consisting of 13 farmers led by Mr. I Made Suastika. The products they produce include lemon fruit, grafted seedlings, and organic fertilizer. There are several issues related to the management of this business, namely the lack of financial record-keeping, the absence of a promotional system to market their products, and production equipment that is already in disrepair. The activities conducted to assist this lemon farmer group include providing training and support for simple financial record-keeping, creating an online marketing promotion strategy, and procuring some new equipment. The goal of this service activity is to enhance the partners' understanding of business financial record-keeping and marketing, as well as to improve their production capacity. The expected outcomes of this activity include the implementation of simple bookkeeping, increased business turnover, production volume, and market share. The targets to be achieved are: enhanced competitiveness, increased turnover and added value for UMKM, application of science and technology in UMKM, publication in national/international journals, online media publication, and uploading videos on YouTube channels